The Lexico Grammatical Features of the Political Register Analysis in the Editorial of the Jakarta Post Newspaper - Dewi Yana (English Department, University of Riau Kepulauan, Batam,Indonesia, 2015)
This research entitled ”The Lexico Grammatical Features of The Political Registers Analysis in The Editorials of The Jakarta Post newspaper 2005” is intended to describe the political register in the editorials of the Jakarta Post particularly the lexemes of political registers and its types of meaning according to Leech. The object of the research is the registers in the editorials of the Jakarta Post newspaper March-May 2005. In collecting the data, the researcher uses the noting techniques by taking a note. In doing the analysis, the researcher applies the descriptive method to describe and to analyze all the data, because the data of this research are in the form of words, phrases, and sentences. Based on the result of the research, there are four parts of speech of lexemes which are found in the editorial of the Jakarta Post newspaper March-May 2005. There are 11 words of verb lexeme with the frequency of occurrence 8.16%, 44 words of noun lexeme with the frequency of occurrence 83 %, 8 words of adjective lexemes with the frequency of occurrence 8.2 %, and there is one word of adverb lexeme with frequency of occurrence 0.3 %. So, there are 64 terms of political registers with the total frequency 324 times. There are two types of meaning found in the sentences written in the editorial of the JP. Those two meanings are conceptual meaning and reflected meaning. There were no connotative, stylistic, affective, collocative and thematic meaning found in this research. Because those five types of meaning do not fulfill the criteria needed to express something in relation to the political language aims.Key Words: Lexico Grammatical Features; Political Register; and Jakarta Post Newspaper